Interleukin-7 and -15 maintain pathogenic memory Th17 cells in autoimmunity. (February 2017) - Chen, Yihe; Chauhan, Sunil K.; Tan, Xuhua; Dana, Reza
Abstract: Th17 cells are principal mediators of many autoimmune conditions. Recently, memory Th17 cells have been revealed as crucial in mediating the chronicity of various refractory autoimmune disorders; however, the underlying mechanisms maintaining memory Th17 cells have remained elusive. Here, using a preclinical model of ocular autoimmune disease we show that both IL-7 and IL-15 are critical for maintaining pathogenic memory Th17 cells. Neutralization of these cytokines leads to substantial reduction of memory Th17 cells; both IL-7 and IL-15 provide survival signals via activating STAT5, and IL-15 provides additional proliferation signals via activating both STAT5 and Akt. Topical neutralization of ocular IL-7 or IL-15 effectively reduces memory Th17 cells at the inflammatory site and draining lymphoid tissues, while topical neutralization of IL-17 alone, the major pathogenic cytokine secreted by Th17 cells, does not diminish memory Th17 cells at the draining lymphoid tissues. Our results suggest that the effective removal of pathogenic memory Th17 cells via abolishing environmental IL-7 or IL-15 is likely to be a novel strategy in the treatment of autoimmune diseases. Highlights: Pathogenic memory Th17 cells express both IL-7 and IL-15 receptors. Neutralization of local IL-7 or IL-15 diminishes memory Th17 cells in autoimmunity. IL-7 and IL-15 maintain pathogenic memory Th17 cells via STAT5 and Akt. Targeting IL-7 and IL-15 may be useful for treating Th17 cell-mediated autoimmunity.